Decomposition and Mineralization of Dimethyl Phthalate in an Aqueous Solution by Wet Oxidation - Dar-Ren Ji; Chia-Chi Chang; Shih-Yun Chen; Chun-Yu Chiu; Jyi-Yeong Tseng; Ching-Yuan Chang; Chiung-Fen Chang; Sheng-Wei Chiang; Zang-Sie Hung; Je-Lueng Shie; Yi-Hung Chen; Min-Hao Yuan (The Scientific World Journal)
Dimethyl phthalate (DMP) was treated via wet oxygen oxidation process (WOP). The decomposition efficiency ηDMP of DMP and mineralization efficiency ηTOC of total organic carbons were measured to evaluate the effects of operation parameters on the performance of WOP. The results revealed that reaction temperature T is the most affecting factor, with a higher T offering higher ηDMP and ηTOC as expected. The ηDMP increases as rotating speed increases from 300 to 500 rpm with stirring enhancement of gas liquid mass transfer. However, it exhibits reduction effect at 700 rpm due to purging of dissolved oxygen by overstirring. Regarding the effects of pressure PT, a higher PT provides more oxygen for the forward reaction with DMP, while overhigh PT increases the absorption of gaseous products such as CO2 and decomposes short-chain hydrocarbon fragments back into the solution thus hindering the forward reaction. For the tested PT of 2.41 to 3.45 MPa, the results indicated that 2.41 MPa is appropriate. A longer reaction time of course gives better performance. At 500 rpm, 483 K, 2.41 MPa, and 180 min, the ηDMP and ηTOC are 93 and 36%, respectively.